MAT161 – Elementary Statistics - PPSM, Pusat Pengajian Sains Matematik (2022)
First Semester Examination 2021/2022 Academic Session FEBRUARY 2022 MAT161 – Elementary Statistics Duration : 2 hours 45 minutes